VERTIGO AS AN INITIAL MANIFESTATION OF CHRONIC CEREBELLAR ABSCESS- CASE REPORT - Ristik-Stomnaroska, Daniela; Aleksovska, Angela; Veljanovski, Dimitar (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Chronic cerebellar abscess is a rare clinical condition, considering the protective function of the blood-brain barrier. The prevalence of brain abscess is increasing with the increase in the number of people living with HIV, especially abscesses caused by a fungal infection. We present the case of a 67 year old male patient with acute onset of dizziness, associated with nausea, vomiting and unstable gait. Initial neurological examination revealed dysarthric speech, with discrete central paresis of the facial nerve, latent left-sided ataxic hemiparesis. In order to clarify the etiology of the expansive change in the left cerebellum, a series of examinations were performed. MRI of the brain was performed with IV contrast, which showed an oval intraaxial lesion with a maximum diameter of 20 x16 mm, on the left cerebellar side. Routine biochemical analyzes was normal, Immunoassay analysis of serum detected a multiple increase in the serum concentration of Immunglobulin E. In consultation with an infectologist, several samples of cerebrospinal fluid were sent for microbiological, parasitological (antibodies to toxoplasmosis, echinococcus and cysticercosis) and serological analysis. The patient was referred to a hematologist again, when a PET scan was performed which showed the presence of metabolically inactive lymph nodes, the same with benign characteristics. A craniotomy and surgical extirpation of the lesion were performed in consultation with a neurosurgeon. The treatment of brain abscesses is multidisciplinary and includes: a neurologist, infectologist, radiologist, neurosurgeon and an internal medicine specialist. Keywords: brain abscess, magnetic resonance imaging.